Fabrication and experiment of an electrical generator for sea wave energy - Hai, Nguyen Van; Anh, Nguyen Dong; Hieu, Nguyen Nhu (Vietnam Journal of Science and Technology, 2017)
This paper presents some results of fabrication and experiment of an electrical generator for sea wave energy. The electrical generator device is fixed on the bottom of the sea and works in the vertical direction of sea waves. The experiment results show that, for the received voltage and current, the power of the electrical generator is up to 300 W and operates stably at about 200 W during experiment at sea. The output voltage is at 220 VAC frequency 50 Hz and is a pure sine wave.